Peculiarities of communication with a pediatric patient. - Романенко, Світлана; Kachalova, Ольга (Psychosomatic Medicine and General Practice, 2024)
Abstract: The highly qualified activity of a pediatrician includes both the possession of proper medical knowledge and skills, and the ability to communicate with sick children and their parents as efficiently as possible. It is communication skills that make it possible to build an effective model of communication between medical staff and patients. Therefore, during the training of medical students at clinical departments, it is necessary to develop the abilities of future doctors to interact, listen, to be able to hear the interlocutor, as well as to simultaneously develop the skills of generalization and analysis of the received information. Communicative competence of a pediatrician, like a doctor of another profile, is a skill that begins to develop during the training process and continues to be formed throughout life with the awareness that effective communication skills are important in the work of the doctor and the patient to achieve compliance with the patient's therapy.